Polymerization shrinkage-stress of short fiber-reinforced composite - Viktória Néma; Tekla Sáry; Lili Fanni Szántó; Gábor Braunitzer; Márk Fráter (Hungarian Dental Association, 2022)
Background: Polymerization shrinkage-related stress of dental composite materials is a clinically relevant problem. In the presence of proper adhesion, shrinkage produces stress in the remaining tooth structure. The greater the destruction, the less the tooth structure is available to withstand the stress; thus, causing cracks in the enamel. The purpose of this in vitro study was to investigate the number of cracks caused by polymerization shrinkage using two different filling techniques utilising short fibre-reinforced composite (SFRC). Materials and methods: 40 extracted wisdom teeth, prepared with standardized MOD cavity (5 mm deep and 2,5 mm wall thickness) were used. After adhesive treatment, teeth were divided into two groups, each restored with SFRC as follows: Group 1: Bulk-fill technique; Group 2 oblique layering technique (with 2 mm increments). In all specimens, the SFRC was covered with 1 mm packable composite resin. After completion of the restoration, the enamel was examined using a D-Light Pro lamp, and the cracks were documented. In addition, the number of the cracks was further documented after 1 week period. Results: There was no significant difference between the groups in respect of the cracks' number. After 1 week, the average number in group 1 was 4.95 showing 340% increase, and in Group 2: 4.30 showing the same 340% increase, which significantly differs to the previously obtained values (p = 0.000). There is no significant difference between the techniques regarding total sum of cracks after 1 week. Conclusions: In both techniques, almost an equal number of cracks is developing. During the post-polymerization period, the number of cracks grows significantly irrespective of the chosen technique.